The effect of substrate surface roughness on GaN growth using MOCVD process - Kum, DW; Byun, DJ (MINERALS METALS MATERIALS SOC, 1997)
Efficiency and lifetime of light emitting diodes and laser diodes inversely depend on defect density of the crystal, and reduction of defect density is accomplished by a proper choice of substrate or a deliberate modification of the substrate surface. Buffer growth or nitridation can yield an atomically flat surface and the roughness of a substrate surface for GaN deposition can be controlled by either method such that lateral film growth can be promoted, The effect uf nanoscale surface roughness on photoluminescence, and crystal quality of GaN/Al2O3, (0001) has boon studied. The optimal conditions for N-2-nitridation or/and GaN-buffer growth correlate well with the minimum surface roughness and surface morphology as determined by atomic force microscopy and it is suggested that, this can be used for process optimization of GaN film growth.
Keywords: OPTICAL-PROPERTIES; GALLIUM NITRIDE; BUFFER LAYER; SAPPHIRE; DEVICES; FILMS